Evolution and Functional Divergence of the Fructokinase Gene Family in Populus - Xu, Weijie; Zhao, Yiyang; Chen, Sisi; Xie, Jianbo; Zhang, Deqiang (Frontiers in Plant Science, 2020)
New kinase has emerged throughout evolution, but how new kinase evolve while maintaining their functions and acquiring new functions remains unclear. Fructokinase (FRK), the gateway kinase to fructose metabolism, plays essential roles in plant development and stress tolerance. Here, we explored the evolution of FRK gene family in 20 plant species (from green algae to angiosperms) and their functional roles in Populus. We identified 125 putative FRK genes in the 20 plant species with an average of 6 members per species. Phylogenetic analysis separated these 125 genes into 8 clades including 3 conserved clades and 5 specific clades, the 5 of which only exist in green algae or angiosperms. Evolutionary analysis revealed that FRK genes in ancient land plants have the largest number of functional domains with the longest amino acid sequences, and the length of FRK genes became shorter during the transition to vascular plants. This was accompanied by loss, acquisition, and diversification of functional domains. In Populus, segmental duplication appears to be the main mechanism for the expansion of FRK genes. Specially, most FRK genes duplicated in salicoids are regulated by Populus-specific microRNAs. Furthermore, compared with common FRKs, Populus-specific FRKs have showed higher expression specificity and are associated with fewer growth and wood property traits, which suggests that these FRKs may have undergone functional divergence. Our study explores the specific roles of FRKs in the Populus genome and provides new insights for functional investigation of this gene family.